PEOPLES’ HADITH IN DATING HADITH DISCUSSION: Reviewing Another Way to Track the Initial Tradition - Muna, Moh. Nailul (Ilmu Hadis, Fakultas Ushuluddin, Universitas Islam Negeri (UIN) Sunan Kudus, 2022)
This study aims to explain and assess the Peoples' Hadith as part of a historical approach that can be used in Dating Hadith. The criticism of the inauthenticity of the hadith has been widely discussed by skeptical orientalists. The most basic reason for this doubt is that there are no written hadith documents in the era of the Prophet that can be known in the present era. The method they use is the dating of hadith; a method that seeks to find out the source of the earliest hadith documents by determining their age and origin. So far, the dating efforts made by Motzky and Nabia Abbott ended in the 2nd century AH. The difference of a century makes this effort still not sufficient to provide an absolute refutation of orientalist skepticism. Based on the descriptive-analytical method, the author finds that People's Hadith has a novelty in terms of viewpoint in the form of the need to look at document sources in the 1st century AH. through communities outside of Muslims, especially the Bedouin. Due to the widening of the scope of this historical search, the implication that will arise is the discovery of prophetic documents that will be obtained by historians or Islamic scholars with sources that come from the Prophet’s Era in the 7th century AH.[Ahli Hadis dalam Diskursus Penanggalan Hadis: Meninjau Cara Lain untuk Melacak Tradisi Awal. Kajian ini bertujuan untuk menjelaskan dan menilai Peoples’ Hadith sebagai bagian dari pendekatan sejarah yang dapat digunakan dalam Dating Hadith. Kritik terhadap ketidak-otentikan hadis telah banyak didiskusikan oleh skeptical orientalists. Alasan yang paling mendasar dari keraguan tersebut sebab tidak adanya dokumen hadis tertulis di era Nabi yang bisa diketahui di era sekarang. Metode yang mereka gunakan yakni dating hadith; sebuah metode yang berupaya mencari tahu sumber dokumen hadis paling awal dengan penentuan umur dan asal-muasalnya. Sejauh ini, upaya dating yang dilakukan oleh Motzky dan Nabia Abbott berakhir pada abad ke 2 H. Adanya selisih satu abad menjadikan usaha tersebut masih tidak cukup untuk memberikan sanggahan penolakan yang mutlak atas keskeptisan orientalis. Berdasarkan metode deskriptif-analitis, penulis menemukan bahwa Poeples’ Hadith memiliki kebaharuan dari segi viewpoint berupa perlunya memandang sumber dokumen abad ke 1 H. melalui komunitas-komunitas yang berada di luar muslim, terutama kepada suku Badui. Oleh karena melebarnya ruang lingkup penelusuran sejarah ini, implikasi yang akan muncul yakni adanya penemuan-penemuan dokumen nabi yang akan didapatkan oleh para ahli sejarah atau pengkaji islam dengan sumber yang memang berasal dari Nabi pada abad ke-7 H.]